Organic food production in a school environment: a case study in the city of Caxias do Sul / RS (Research, Society and Development, 2022)
The main purpose of using pedagogical vegetable gardens is to carry out an educational program, with the school garden as an organizing axis, allowing the systematic study and integration of cycles, processes, and dynamics of natural phenomena. In this sense, the general objective of this work was the organization of vegetable gardens, medicinal garden / human body clock, as well as orchards, fields, gardens, and cacti, as well as the maintenance of all these spaces at the Instituto de Educação Cristóvão de Mendoza, located in Caxias do Sul/RS. This work is a strategy that enables extension and learning, with planting, management, and production without agrochemicals, thus actively fostering participatory citizenship among students, teachers, and school staff. Although school gardens are not a novelty in the scenario of health education or Food and Nutrition Education, there is still little discussion about their approaches and educational possibilities. The project also assumes environmental and social responsibility, providing the rescue of students' knowledge, in relation to the contents to be worked on, constituting the starting point for the teaching, and learning process.